ANALYSIS OF ARABIC TEACHING BOOKS IN CLASS IX MADRASAH TSANAWIYAH PUBLIC OF THE MINISTRY OF RELIGION (THE REPUBLIC OF INDONESIA IN 2019) - Hafizatur Rahmi; Samir Alsayed Abdelmotalleb Ali Zaher; Slamet Daroini (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2022)
The Purpose Of This Study Was To Find Out The Feasibility Of The Content, Material, Presentation, Graphics Aspects In The 2019 Class IX Madrasah Tsanawiyah Arabic Textbooks Published By The Ministry Of Religion Of The Republic Of Indonesia. This Analysis Uses The Reference Of The National Education Standards Agency Abbreviated As BSNP Regarding The Feasibility Of Teaching Materials. The Research Approach Used A Qualitative Approach With Content Analysis Data Analysis And For Data Collection Techniques Using Library Research Methods, The Data Sources Used In This Study Used 2 Types Of Sources Including Primary Arabic Madrasah Tsanawiyah Class IX Published By The Ministry Of Religion Of The Republic Of Indonesia Year 2019 And Secondary, Namely Journals , Other Documents. The Results Of This Study Reviewed Books From The Content Aspect, The Results Of The Analysis In The Section On National Values And Norms, As A Whole Avoided Elements Of Impropriety, The Aspect Of The Language Used Seemed Quite Understandable To Students. Presentation Aspect, This Book Has Presented Related To Basic Competencies, Maps, Illustrations At The Beginning Of Each Chapter, Transliteration, The Graphical Aspects Used In This Book Are Quite Complex الغرض من هذا البحث هو معرفة جدوى جوانب المحتوى، والمواد، والعرض التقديمي، والرسومات في كتب اللغة العربية المدرسية لمدرسة تسناوية الفئة التاسعة الصادرة عن وزارة الدين في جمهورية إندونيسيا في عام 2019. يستخدم هذا التحليل مرجع وكالة معايير التعليم الوطنية، والمختصرة باسم BSNP ، فيما يتعلق بجدوى المواد التعليمية. يستخدم منهج البحث منهجًا نوعيًا مع تحليل بيانات تحليل المحتوى ولأغراض جمع البيانات باستخدام أساليب البحث في المكتبات، تستخدم مصادر البيانات المستخدمة في هذه الدراسة نوعين من المصادر بما في ذلك اللغة العربية الأساسية المدرسة التسناوية من الدرجة التاسعة الصادرة عن وزارة الدين في جمهورية مصر العربية. جمهورية إندونيسيا في عام 2019 والثانوي، وهي المجلات والوثائق الأخرى. استعرضت نتائج هذه الدراسة الكتاب من جانب المحتوى، ونتائج التحليل في القسم الخاص بالقيم والمعايير الوطنية، والعناصر التي تم تجنبها بشكل عام من عدم اللائق، وبدا جانب اللغة المستخدمة مفهومة تمامًا من قبل الطلاب. من حيث العرض، قدم هذا الكتاب فيما يتعلق بالكفاءات الأساسية، والخرائط، والشروحات التوضيحية في بداية كل فصل، والترجمة الصوتية، والجوانب الرسومية المستخدمة في هذا الكتاب معقدة للغاية